Analisis Sistem Kendali Kokoh pada Sistem Non Linier dengan Pendekatan Pertidaksamaan Matriks Non Linier - Asep Najmurrokhman (Fakultas Teknik - Universitas Jenderal Achmad Yani, 2002)
This paper proposes about robust control systems analysis for a class of nonlinear systems using nonlinear matrix inequalities approach. Robustness corresponds with appropriately disturbance suppression. Controller that renders robustness property of the system is developed with solving solvability condition in advance. Such condition is described by three nonlinear matrix inequalities. Computational aspect is considered to solve these matrix inequalities.